Application of Subcritical Water Hydrolysis (SCW) in Producing Reducing Sugar for Biofuel Production - Dian Ranggina; Maria Assumpta Nogo Olea; Hanny F. Sangian; Arief Widjaja; Hijrah Amaliah Azis (Equilibrium Journal of Chemical Engineering, 2024)
Abstract. This work aimed to produce reducing sugar from coconut husk using subcritical water hydrolysis. Coconut husk contains cellulose and hemicellulose that can be converted into reducing sugars and then fermented into biofuel. In this study, the subcritical water hydrolysis was carried out in a batch reactor at  temperatures 120-260 oC and pressures, 40, 80, and 160 bar for 1 h. Subcritical water method obtained two products, namely (a) liquid containing sugar and (b) solid containing cellulose, hemicellulose and lignin. The liquid sugars were analyzed by HPLC and DNS, while crystal structure was characterized by XRD and SEM. The highest yield of reducing sugar obtained was 0.25 g/g cellulose+ hemicellulose at 150 oC and 80 bar.Keywords: Biofuel, Coconut husk, Lignocellulose, Reducing sugar, Subcritical water